2019
DOI: 10.1029/2018ja026048
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Small‐Scale Gravity Wave Activity in the Ionosphere During the Major Sudden Stratospheric Warming Event of 2009

Abstract: The present study investigates the effect of the major sudden stratospheric warming (SSW) event of 2009, on the small‐scale gravity wave (GW) activity in the ionosphere. Small‐scale fluctuations with time periods within the range of 10–90 min observed in Global Positioning System total electron content (TEC) data have been used as a proxy for GW activity in the ionosphere. TEC data from five longitudinally separated Global Positioning System stations located around 60∘N latitude have been utilized for this pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 101 publications
2
24
0
Order By: Relevance
“…Using the SABER measurement aboard the TIMED satellite, Pancheva and Mukhtarov (2011) investigated the behavior of the SW2 in the MLT. There, the typical observed peak values for the SW2 amplitudes are situated at low latitudes during the June solstice: 25-28 K at 15-30 • N and 15-20 K at 15-25 • S. In our study, GCM simulations based on two different GW parameterizations yield different results for the SW2 tide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the SABER measurement aboard the TIMED satellite, Pancheva and Mukhtarov (2011) investigated the behavior of the SW2 in the MLT. There, the typical observed peak values for the SW2 amplitudes are situated at low latitudes during the June solstice: 25-28 K at 15-30 • N and 15-20 K at 15-25 • S. In our study, GCM simulations based on two different GW parameterizations yield different results for the SW2 tide.…”
Section: Discussionmentioning
confidence: 99%
“…The amplitude maximizes at around a 125 km height. The maxima are 41 K at 15 • S and 38 K at 20 • N. The peak of the SW2 amplitude above a 200 km height (34 K) appears at 15-25 • S, and the secondary peak (10 K) is found around 45 • N. Using the SABER (Sounding of the Atmosphere using Broadband Emission Radiometry) measurement aboard the TIMED (Thermosphere Ionosphere Mesosphere Energetics Dynamics) satellite, Pancheva and Mukhtarov (2011) Forbes et al, 2011). The simulated SW2 in the SH (NH) is larger (smaller) than the observed SW2.…”
Section: Migrating Semidiurnal Tidementioning
confidence: 99%
“…During minor warming, thermospheric GWs activity can be enhanced significantly (e.g., Yiğit et al, 2014;Yiğit and Medvedev, 2016), while during major warmings it may encounter a decrease (Nayak and Yiğit, 2019). Here, we used a whole atmosphere GCM incorporating a whole atmosphere GW parameterization in order to the study the mean dynamical effects of GWs and their impact on the semidiurnal tides in the thermosphere.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, the aeronomy community has come to the realization that SSWs can be a significant source of ionospheric variability (Chau et al, ; Pedatella et al, ). In particular, the January 2009 major Arctic SSW, which took place under extremely quiet solar and geomagnetic activity conditions, enabled many studies to attribute observed ionospheric perturbations to the SSW (e.g., Chau et al, ; Goncharenko et al, , ; Fejer et al, ; Liu et al, ; Lin et al, ; Nayak & Yiğit, ; Oyama et al, ; Pedatella & Forbes, ; Patra et al, ; Pancheva & Mukhtarov, ; Rodrigues et al, ; Yue et al, ; Yadav et al, ). Most studies concentrated on the dayside low‐latitude region, where the ionospheric response to the SSW was most pronounced.…”
Section: Introductionmentioning
confidence: 99%